If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9u-9(2u+4)+8=0
We simplify the equation to the form, which is simple to understand
9u-9(2u+4)+8=0
Reorder the terms in parentheses
9u+(-18u-36)+8=0
Remove unnecessary parentheses
+9u-18u-36+8=0
We move all terms containing u to the left and all other terms to the right.
+9u-18u=0+36-8
We simplify left and right side of the equation.
-9u=+28
We divide both sides of the equation by -9 to get u.
u=-3.11111111111
| 4(2x+3)-7=13 | | 6d+8=5d+11 | | 4(x-9)=-14.8 | | -6x-8=10 | | 6x-29=4x+12 | | m^4-4n^2=0 | | 11=x-3 | | 6(a+2)=38.4 | | x+6=91 | | 83.5=9c-2 | | -8(x+4)=10x+4 | | 4e-9=23.8 | | 7w^2-28w+28=0 | | 3p=17.1 | | -15x+8=-15x+8 | | -15x+8=-15x-8 | | 7y+12x-5=0 | | 5(a+4)=65 | | z^6+6z^3+8=0 | | 4r=155 | | 8e-3=29 | | 2x^3+20=5x^2+8x | | 16x+12=9x+33 | | 6x-21=33-9x | | x-7=-42 | | 185-5x=40x+20 | | 10-9x=82-37x | | X*.3=70 | | x-21=18 | | 9-12x+5x=14+2 | | 10x-2=6x+7 | | 3*(75+x)+x=850 |